A França Antártica e a criação de padrões narrativos sobre o Brasil e os brasileiros - França, Jean Marcel Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
O objetivo deste pequeno ensaio é analisar as narrativas derivadas da primeira experiência colonizadora francesa no Novo Mundo, a França Antártica, com o intuito de demarcar em tais escritos certos padrões narrativos acerca da América e dos seus habitantes, os ditos selvagens. Buscaremos demonstrar que tais padrões, estabelecidos de maneira pioneira pelos gauleses, tiveram vida longa nas narrativas posteriores com menções ao Brasil e aos seus habitantes.

The objective of this short essay is to analyze the historical accounts originating from the first French colonization attempt in the New World, the French Antarctic, with the purpose of defining in such writings certain patterns about America and its inhabitants, the so-called savages. We sought to demonstrate that such patterns, established in a pioneering way by the Gauls, had a long life in the subsequent accounts where Brazil and its inhabitants were mentioned.
The French Antarctic and the creation of patterns pertaining to historical accounts concerning Brazil and Brazilians
Keywords: França Antártica; Narrativas; Colonização Francesa; French Antarctic; Historical Accounts; French Colonization